The physicochemical properties, in vitro binding capacities and in vivo hypocholesterolemic activity of soluble dietary fiber extracted from soy hulls. Issue 12 (3rd November 2016) - Liu, Chun; Lin, Xiao-Lu; Wan, Zhili; Zou, Yuan; Cheng, Fen-Fen; Yang, Xiao-Quan
Abstract : Soy hull soluble dietary fiber possessed favorable in vitro binding capacities and in vivo hypocholesterolemic activity. Abstract : Soluble dietary fibers (SDFs) have earned a healthy reputation due to their distinguished physiological functions. In this study, SDF was efficiently extracted from soy hulls using a phosphate-assisted subcritical water extraction method. The physicochemical properties, in vitro binding capacities and in vivo hypocholesterolemic activity of soy hull soluble dietary fiber (SHSDF) were evaluated. The results indicated that the major component of SHSDF was pectic polysaccharides, and with comparison to commercial oat β-glucan, SHSDF had favorable solubility, viscosity, water-holding ability (5.26 g water per g sample), and oil holding capacity (4.83 g oil per g sample). It also possessed good in vitro cholesterol-binding capacity (6.18 mg g −1 sample at pH 2 and 7.62 mg g −1 sample at pH 7), bile acid-binding capacity (3.3, 1.73 and 6.65 μM of GCA, GCDCA and GDCA per 100 mg of sample), glucose dialysis retardation index (64.76%), and in vivo hypocholesterolemic activity (16.88% and 35.28% reduction in serum total cholesterol and LDL level in rats, respectively). These data suggest that SHSDF has great potential in food applications, especially in the development of functional food ingredients.